Desenvolvimento de um sistema de informação e alerta precoce da seca e elaboração de estratégias de planejamento proativo de adaptação às secas urbanas - Araújo Júnior, Luiz Martins de (2018)
The objective of this work is to create an Information System and Early Warning of Drought (SIAPS), based on the monitoring and prediction of hydrometeorological variables and drought indexes, in order to support the elaboration of adaptive urban drought planning. The place of development of this study is the Metropolitan Jaguaribe System. The study uses different methods of forecasting inflows and / or volumes in the basin of the application region. The methods used were: dynamic downscaling coupled to the rainfall-flow hydrological model, SMAP, a semi-parametric method based on a re-sampling technique of the historical flow series and a method based on neural network technique. From these prediction methods was made a multi-model ensemble known as pooled ensemble and a performance test of the multi-ensemble was also performed. Then, predicted flow data from the ensemble served as input for a model of operation of reservoirs model of operation of reservoirs capable of receiving the predicted flows and given the current volume of the Jaguaribe-Metropolitan System to predict the target levels (NM) and rationing Level (Nrac) that served as indicators of current and future drought conditions. The thresholds for each drought state (Normal, Pre-Alert, Alert, Emergency I and Emergency II) given by the operating model targets will serve as triggers for triggering mitigation and drought response actions. With the computation of NM and Nrac, it was possible to integrate the monitoring and forecasting data, allowing the identification of hydroclimatic vulnerabilities and the development of a drought risk aversion planning matrix. In this way, it is possible to conclude that the SIAPS proposed here allows an advance in the management of droughts, allowing the previous identification of vulnerabilities of the water system, as well as serving as support for the elaboration of adaptive urban drought planning, making it possible for decision makers to use a drought risk management vision, which enables proactive actions of mitigation and response, breaking a historical cycle of reactive actions of combat and coexistence with the drought